PENGARUH PERSEPSI AKUNTANSI, PENGETAHUAN AKUNTANSI DAN SKALA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN DIMEMBE: Usaha Mikro Kecil Menengah - Kaligis, Stevie; Christina Lumempouw (Program Studi Akuntansi Universitas Pasir Pengaraian, 2021)
The purpose of this study was to determine: (1) whether there is a significant positive effect of accounting perception on the use of accounting information, (2) whether there is a significant positive effect of accounting knowledge on the use of accounting information, (3) whether there is a significant positive effect of business scale on the use of accounting information. accounting information. The sampling method used is Non Probability Sampling with the sampling technique used is Purposive Sampling. Data collection techniques by distributing questionnaires, interviews and literature study. The data analysis used in this study is multiple linear regression analysis using SPSS version 24. Based on the results of the research conducted, it shows that the perception of accounting has a significant positive effect on the use of accounting information with the Sign value. 0.000 <0.05 and t arithmetic value 4.152 > t table 2.020, accounting knowledge has a significant positive effect on the use of accounting information with a Sign value. 0.001 <0.05 and the t-count value is 3.536 > t-table 2.020. While the business scale does not significantly affect the use of accounting information with a Sign value. 0.975 > 0.05 and the t-count value is 0.031 < 2.020. And the simultaneous test shows that accounting perception, accounting knowledge and business scale have a significant positive effect on the use of accounting information with sign values. 0.000 < 0.05 and the calculated f value is 43,805 > 3.23.